THE INTEGRATIVE MODEL OF POWER SHARING AND THE LAW ON THE USE OF LANGUAGES- THE CASE OF MACEDONIA - Runcheva Tasev, Hristina (International Academic Institute, 2019)
The paper analyses the extent to which the integrative theory, pioneered by Donald Horowitz, has been incorporated in the new Law on the use of languages in the Republic of Macedonia. Given Macedonia’s distant and near past, the theory is applicable in the analysis of laws and policies aiming towards greater integration of ethnic minorities. The paper focuses on the ethnicity, its formation, and builds connections with the reasons for emergence of ethnic conflicts. It analyses politics of symbols as the essence of interethnic politics, and the status of one group’s language as a direct indicator of the status of the group itself. Using the Horowitz’s integrative theory, elaborating its essence, scope, methods, the author applies the theoretical findings on the Macedonia’s case of ethnic conflict in 2001. The Ohrid Framework Agreement that finalized the conflict is used as a basis for the Law on languages. The integrative capacity of the law itself is analyzed through the prism of its provisions and political circumstances in the country.
Keywords: integrative theory, law on languages, Macedonian case, Ohrid Framework Agreement